Interannual Nearshore Habitat Use of Young of the Year White Sharks Off Southern California - Anderson, James M.; Burns, Echelle S.; Meese, Emily N.; Farrugia, Thomas J.; Stirling, Brian S.; White, Connor F.; Logan, Ryan K.; O’Sullivan, John; Winkler, Chuck; Lowe, Christopher G. (Frontiers in Marine Science, 2021)
Young-of-the-year (YOY) and juvenile-stage white sharks may use southern California nearshore beach habitats more extensively than previously known, within meters of some of the most heavily used beaches in the world. Such knowledge forms a critical component of species management and conservation plans, in addition to public safety and risk mitigation planning. We used data derived from a combination of satellite tag locations (13 animals over 3 years) and passive acoustic monitoring (34 animals over 8 years) to examine the occurrence, relative abundance, and residency patterns of YOY white sharks in southern California waters. Our results suggest that southern California contains spatiotemporally dynamic centers of primary nursery habitat. Tagged YOY white sharks formed loose aggregations at “hotspot” locations that were interannually variable, where individuals exhibited temporal fidelity, higher levels of residency, and spatially restricted movements, with multiple YOY individuals simultaneously displaying this behavior. While models of biotic and abiotic variables suggested relative abundance of tagged sharks may be predicted by sea surface temperature, salinity and productivity (chlorophyll-A), these predictors were not consistent across all years of the study. Thus, novel approaches that incorporate technologies to derive high resolution environmental data, paired with more comprehensive telemetry datasets are therefore required to better understand the extrinsic factors that drive habitat selection and residency patterns in juvenile white sharks.